2014
DOI: 10.1007/s00253-014-6026-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of 3,4-dimethylpyrazole phosphate (DMPP) and dicyandiamide (DCD) on ammonia-oxidizing bacteria and archaea in a vegetable soil

Abstract: Nitrification inhibitors (NIs) 3,4-dimethylpyrazole phosphate (DMPP) and dicyandiamide (DCD) have been used extensively to improve nitrogen fertilizer utilization in farmland. However, their comparative effects on ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in agricultural soils are still unclear. Here, we compared the impacts of these two inhibitors on soil nitrification, AOA and AOB abundance as well as their community structure in a vegetable soil by using real-time PCR and terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 56 publications
9
32
0
2
Order By: Relevance
“…T-RFLP analysis showed that urea addition had a significant impact on the community structure of AOB compared to other treatments (Fig. 4a), which was consistent with previous findings (Jia and Conrad 2009;Chen et al 2015). However, the AOB community composition between the urea + DCD and urea + C 2 H 2 treatments was similar in our study.…”
Section: Aoa-otu7 (256bp)supporting
confidence: 92%
See 2 more Smart Citations
“…T-RFLP analysis showed that urea addition had a significant impact on the community structure of AOB compared to other treatments (Fig. 4a), which was consistent with previous findings (Jia and Conrad 2009;Chen et al 2015). However, the AOB community composition between the urea + DCD and urea + C 2 H 2 treatments was similar in our study.…”
Section: Aoa-otu7 (256bp)supporting
confidence: 92%
“…3a), which was in agreement with previous studies in a large number of agricultural soils (Wu et al 2011;Habteselassie et al 2013;Chen et al 2015). It has been reported that AOB growth is favored by high-N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected (Di et al 2009(Di et al , 2010a.…”
Section: Nitrosospira Nitrososmonassupporting
confidence: 92%
See 1 more Smart Citation
“…AOA did not respond to the application of NH 4 + in the alluvial soil, while it was inhibited with respect to the control in the red soil, thus confirming what it was obtained in agricultural soils (Wu et al 2011;Ai et al 2013;Habteselassie et al 2013;Di et al 2014Di et al , 2014Chen et al 2015). Generally, AOB growth is favored by high NH 4 + -N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected or suppressed (Di et al 2009(Di et al , 2010Di and Cameron 2011;Di et al 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the rising costs of synthetic N fertilizers have strengthened farmers' commercial incentive to reduce N fertilization and as a consequence N losses (Ernfors et al 2014). Nitrification is a critical component in the N cycle, which causes N losses in the form of nitrate (NO 3 − ) leaching and nitrous oxide (N 2 O) emissions from agricultural systems (Wakelin et al 2014;Chen et al 2015). Nitrate leaching could trigger waterway eutrophication and drinking water contamination (Philippot et al 2007).…”
Section: Introductionmentioning
confidence: 99%